Evolutie van de schoonheidsidee in de filosofie. - Michiels, Dirk; Wuyts, Leo F.A. (Mechelen : Galerij Nova, 1972)
De Boeck, Felix ; Massa, Roland ; Camus, Gustave ; Portenaert, Jeanne ; De Bruyn, Jo ; van Mechelen, Gard ; Landuyt, Octave ; Van Tuerenhout, Jef ; Vaerten, Jan ; De Vries, Hubert ; Riedel, Helene ; De Winter, Jan ; Van der Loo, Jan
Nederlands
boek